Female perspective: the burden of Alzheimer's disease and other dementias in China from 1990 to 2019 and prediction of their prevalence up to 2044 - Meng, Wenxin; Xie, Jinping; Yuan, Ni; Liu, Pingyu; Yang, Fan; Jiang, Rong; Hua, Hui (Frontiers in Public Health, 2023)
Background Dementia is more prevalent in women than in men across the world, and sex differences are reflected in the burden of dementia borne by women and men. However, a few studies have specifically analyzed the disease burden of dementia in Chinese women. Objective This article aims to raise awareness of Chinese females with dementia (CFWD), outline an effective response to future trends in China from a female perspective, and provide a reference for the scientific formulation of dementia prevention and treatment policies in China. Methods In this article, epidemiological data on dementia in Chinese women were obtained from the Global Burden of Disease Study 2019, and three risk factors, namely, smoking, a high body mass index, and a high fasting plasma glucose, were selected for the analysis. This article also predicted the burden of dementia in Chinese women in the next 25 years. Results The prevalence of dementia, mortality, and disability-adjusted life year rates increased with age in CFWD in 2019. All three risk factors provided by the Global Burden of Disease Study 2019 showed positive correlations for the effect of disability-adjusted life years (DALYs) rates on CFWD. Among them, a high body mass index had the greatest effect (8%) and smoking had the smallest effect (6.4%). Over the next 25 years, the number of CFWD and its prevalence are expected to be on the rise, while mortality is expected to remain relatively stable and decline slightly, but deaths from dementia will continue to increase. Conclusions The situation arising due to the spread of dementia among Chinese women in the future is going to become a serious issue. To reduce the burden of dementia, the Chinese government should prioritize its prevention and treatment. A multi-dimensional, long-term care system involving families, community, and hospitals should also be established and supported.